KOORDINASI KOMITE SEKOLAH DI SMA NEGERI 7 KOTA PONTIANAK - Angga Sofiana Putra E.21108008 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Implementation of the School Committee give greater autonomy to schools. Schools have the authority and greater responsibility in managing the school, making it more independent. This study focused on the division of labor, unity of direction and actions, and cooperative relations. Foci are discussed with qualitative methods and case studies in SMAN 7 Pontianak. From the research it was found that the division of labor, unity of direction and action, cooperation has not terlaksan as expected. Therefore, the focus of the division of tasks researchers suggest that more attention to the quality and quantity of the board but how to carry out its duties and functions. Suggestions for the direction and focus of unity of action is expected to implement the unity of action by way of joint meetings. As for the suggestion to focus cooperation should have mutual understanding, co-exist, help each other, and complement each other so that the School Committee program objectives in order to achieve educational services as predefined. Keywords: Coordination Committees School, Division of Labor, Unity of Direction and Action, Equal Employment